2006
DOI: 10.1002/jclp.20272
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of therapist treatment effects: Toward providing feedback to individual therapists on their clients' psychotherapy outcome

Abstract: This study examined data collected on over 5,000 clients seen by 71 therapists over a 6-year period in a University Counseling Center. Clients were given the Outcome Questionnaire-45 (OQ-45) on a session-by-session basis to track their treatment response. Data were also collected on therapists' theoretical orientation, years of experience, gender, and type of training. Data were analyzed using hierarchical linear modeling (HLM) to see if general therapist traits (i.e., theoretical orientation, type of training… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
154
3
9

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(175 citation statements)
references
References 27 publications
9
154
3
9
Order By: Relevance
“…In contrast to the results from RCTs, naturalistic studies drawing on data from routine practice have tended to indicate consistent therapist effects in the region of 5%-8% of the variance in outcome explained (e.g., Baldwin & Imel, 2013, Brown, Lambert, Jones, & Minami, 2005Lutz, Scott, Martinovich, Lyons, & Stiles, 2007;Okiishi, Lambert, Eggett, Nielson, Vermeersch & Dayton, 2006;Saxon & Barkham, 2012). In a context where therapy is being delivered in routine practice and therapists may not be implementing protocol-driven interventions, the resulting variability in therapist effects appears understandable.…”
Section: Therapist Effects: Trials and Routine Practicementioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the results from RCTs, naturalistic studies drawing on data from routine practice have tended to indicate consistent therapist effects in the region of 5%-8% of the variance in outcome explained (e.g., Baldwin & Imel, 2013, Brown, Lambert, Jones, & Minami, 2005Lutz, Scott, Martinovich, Lyons, & Stiles, 2007;Okiishi, Lambert, Eggett, Nielson, Vermeersch & Dayton, 2006;Saxon & Barkham, 2012). In a context where therapy is being delivered in routine practice and therapists may not be implementing protocol-driven interventions, the resulting variability in therapist effects appears understandable.…”
Section: Therapist Effects: Trials and Routine Practicementioning
confidence: 99%
“…Because of the limited number of PWPs in the current study, patient pre-treatment severity was also controlled for in the modelling. Pre-treatment severity is strongly associated with outcome (Garfield, 1994) and once this is taken into account other variables have little predictive value (Okiishi et al, 2006, Luborsky, McLellan, Diguer, Woody, & Seligman, 1997.…”
Section: Therapist Effects: Methodological Issuesmentioning
confidence: 99%
“…Positions constructed for a female therapist in male batterers' group treatment In psychotherapy research the gender of the therapist has been found a poor predictor of therapy outcome for both male and female clients (Bowman, Scogin, Floyd, & McKendree-Smith, 2001; Okiishi et al 2006). It has been suggested that how the therapist deals with processing gender issues in the therapy session seems to be much more important than the therapist's gender itself (Blow, Timm, & Cox, 2008).…”
mentioning
confidence: 99%
“…Minor differences between professionals and trainees have been found in studies (e.g. Okiishi et al, 2006;Hill & Knox, 2013). More research is needed in this area.…”
Section: The Relationship Between Clients' Personality Traits Workinmentioning
confidence: 99%